Dampak Toxic Friendship pada Remaja Masjid Qutbu Karomatul Atkiya” (Studi Kasus Kegiatan Asrakalan di Kampung Mbah Dalam Kota Bogor) - Imam Syahrul (KOLONI, 2024)
Adolescence is a transition period from childhood to adulthood. Adolescence usually has great energy and turbulent emotions, but imperfect self-control. According to the World Health Organization (WHO, 2020), a person is considered a teenager in the age range of 10-19 years who is experiencing physical, emotional and social changes and is susceptible to mental health problems due to exposure to poverty, abuse and violent behavior. Therefore, it is necessary to monitor the emotional development of children who are starting to grow into teenagers. Adolescents who have detrimental social interaction skills find it difficult to establish friendships and prefer to be alone, like to be hostile, angry, withdrawn, and tend not to have many friends. These problems can disrupt friendships between people and can result in a separate groups into individuals. This problem must also be resolved immediately, otherwise we will definitely be the ones who suffer. Another problem that arises is when we want to get rid of a toxic friend, sometimes we feel sorry for those who used to do everything with us, but are now separated, which makes them lonely. However, if we choose to continue our friendship with someone who is toxic, it will be our party who suffers, both mentally and physically. The research objectives of this study are 1). To find out what causes toxic friendship. 2). To find out what impacts arise from toxic friendship. 3). To find out how to overcome toxic friendship behavior. The approach used by researchers is a qualitative approach with a descriptive method that is flexible, flexible and open, and focuses more on describing the toxic phenomenon that is the focus of the research, and in its implementation, data and theory are explored as deeply as possible so that the findings can be described in full, In this research, researchers also used the Mils & Hubberman method, the activities were data reduction, data presentation, and drawing conclusions. Data Reduction is conducting research in the field by observing the behavior of teenagers affected by toxic friendship. conducted in-depth interviews with teenage members of the Qutbu Karomatul Atkiya Mosque. Based on research conducted by conducting interviews with several informants who had the required criteria, the results of this research will explain the impact of toxic friendship on teenagers at the Qutbu Karomatul Atkiya Mosque, focusing on several indicators. namely insecurity, depression and low self-confidence. Based on the results of interviews with the subjects, it was stated that Alvin, Reza and Janu were victims of toxic friendship who were affected by several impacts from their own friends.